(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The Role of Theme Parks in Tourism. Theme parks play a significant role in the tourism industry, attracting millions of visitors each year and contributing to the economic growth of destinations. These immersive entertainment destinations offer a unique and memorable experience for tourists of all ages.